Studium produkce extracelulárních polymerů pomocí mikroorganismu Aureobasidium pullulans - Horáček, Pavel (Vysoké učení technické v Brně. Fakulta chemická, 2013)
Diplomová práce se zabývá studiem vlivu podmínek a kultivačního uspořádání na produkci extracelulárních polymerů pomocí kvasinkovitého mikroorganismu Aureobasidium pullulans. Obsahem teoretické části je stručná charakterizace A. pullulans, jeho použití v biotechnologiích a přehled produkovaných látek, zejména pullulanu a kyselině poly-L-jablečné. Náplní experimentální části práce bylo zjištění nejvhodnějších podmínek kultivace A. pullulans CCM 8182. Zjištěné optimální podmínky byly srovnány s průběhem kultivací na odpadních substrátech, které představují levné zdroje živin a umožňují snížení nákladů výroby. Z odpadních substrátů byly použity například ovesné otruby, pohankové slupky, jablečná vláknina a další. Součástí experimentální práce byla optimalizace stanovení obsahu extracelulárních polymerů – pullulanu a kyseliny poly-L-jablečné metodou HPLC. V rámci optimalizace byla navržena vhodná mobilní fáze a podmínky separace produktů hydrolýzy polymerů, tj. glukózy a kyseliny L-jablečné na speciální stacionární fázi (kolona Rezex Roa organic acid H+, 5 mM kyselina sírová, průtok 0,5 mL/min, teplota 60 °C). K nejvyšší produkci pullulanu došlo při kultivaci na ovesných otrubách (13,03 g/L) při počátečním pH 7,5, zatímco nejvyšší produkce kyseliny poly-L-jablečné byla zaznamenána u kultivace na jablečných slupkách (2,89 g/L) při pH 6. Bylo zjištěno, že k vyšší produkci kyseliny poly-L-jablečné došlo při pH 6, zatímco vyšší produkce pullulanu byla při pH 7,5.

The diploma thesis is focused on the study of the influence of cultivation conditions and arrangement for the production of extracellular polymeric substances by using yeast-like microorganism Aureobasidium pullulans. In the theoretical part a brief description of A. pullulans, its use in biotechnology and produced exobiopolymers, especially pullulan and poly-L-malic acid are presented. The first aim of the experimental part was to set the most appropriate cultivation conditions for A. pullulans CCM 8182. Growth and production properties in optimum conditions were compared with cultivation on waste substrates - oat bran, buckwheat husks, apple fiber and others. Waste substrates can be used as cheap nutrient sources which enable reducing cost of potential biotechnological production. As a further part of this work, optimization of HPLC/RI method for analysis of exobiopolymers has been done. Optimal mobile phase composition and chromatography conditions were proposed. Column Roa organic acid H+ was the most suitable for simultaneous separartion of glucose and malic acid. Before HPLC analysis hydrolysis of polymers was done. Sulphuric acid (5 mmol/L) was used as a mobile phase at flow rate 0.5 mL/min and temperature 60 °C. The highest production of pullulan occurred using oat bran as a substarate (13.03 g/L) at an initial pH 7.5. Maximum production of poly-L-malic acid was observed during the cultivation on apple peels (2.89 g/L) at pH 6. It was found that the higher production of poly-L-malic acid occurred at pH 6, while higher production of pullulan was at pH 7.5.
Production of extracellular polymeric substances by Aureobasidium pullulans
Keywords: Aureobasidium pullulans; pullulan; poly-L-jablečná kyselina; Aureobasidium pullulans; pullulan; poly-L-malic acid